Pengaruhkualitas Pelayanan Online Shopee Terhadap Kepuasan Konsumen (Studi Mahasiswa STEBI Tanggamus) - Nirmala Dewi; Masrinah Masrinah (Dinar Islamic Review, 2020)
The purpose of this study was to determine the effect of ShopeeOnline's service quality on consumer satisfaction for students of the Islamic School of Economics and Business. The method used is a quantitative method. The population in this study were students of the Islamic School of Economics and Business who had used the Shopee Online application. Based on Google Forms distributed and available to researchers, it was found that there were 202 students of the Faculty of Economics and Islamic Business who had made online purchases from Online Shopee and the sample used was 134 respondents. The sampling method in this study used the Slovenian formula. Collecting data using library research methods, documentation and questionnaires. The results of the questionnaire were tested for validity and also tested for reliability, in the form of a normality assumption test. The data analysis technique used normality test technique, simple regression. Using the Statistical Product and Service Solution (SPSS) program. The results showed that the proposed hypothesis was accepted because it showed positive and significant hypothesis test results. This means that the quality of online shopping services has a positive and significant effect on consumer satisfaction for students of the Islamic School of Economics and Business.